2021
DOI: 10.1126/sciadv.abk2318
|View full text |Cite
|
Sign up to set email alerts
|

Eccentricity-paced monsoon variability on the northeastern Tibetan Plateau in the Late Oligocene high CO 2 world

Abstract: Precipitation on the NE Tibetan Plateau was driven by combined high- and low-latitude processes during the warm Late Oligocene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(46 citation statements)
references
References 47 publications
5
41
0
Order By: Relevance
“…The possible increase in temperatures during this period and a simultaneous strengthening of summer monsoonal circulation would be expected, since continental summer temperatures govern moist static energy, which in turn controls monsoonal intensity 95 . Therefore, the variability in MAP and weathering intensity in the upper part of the Ulantatal sequence may have originated from the EASM, driven by astronomically forced Antarctic ice sheet oscillations 96 . This is also corroborated by the coupling of aridity events in Ulantatal with the marine oxygen isotope events.…”
Section: Discussionmentioning
confidence: 99%
“…The possible increase in temperatures during this period and a simultaneous strengthening of summer monsoonal circulation would be expected, since continental summer temperatures govern moist static energy, which in turn controls monsoonal intensity 95 . Therefore, the variability in MAP and weathering intensity in the upper part of the Ulantatal sequence may have originated from the EASM, driven by astronomically forced Antarctic ice sheet oscillations 96 . This is also corroborated by the coupling of aridity events in Ulantatal with the marine oxygen isotope events.…”
Section: Discussionmentioning
confidence: 99%
“…Periodic expansion and contraction of the ice sheet could result in periodic variability of sea level, sea surface temperature, intermediate and deep‐water production in the Southern Ocean, and amount of latent heat release (Ao et al., 2021; Nie et al., 2017). These processes further regulate the orbital‐scale changes of the capacity of the monsoon to transport moisture, such as tropical ocean water evaporation and lower‐tropospheric water vapor content affected by temperature, distance of moisture transport pathway from the ocean to the studied areas affected by sea‐level fluctuations and coastline, finally leading to orbital‐scale changes of intensity, northeastern edge, and precipitation extent of the SAM in the central TP (Ao et al., 2021; Nie et al., 2017). Alternatively, eccentricity modulates low‐latitude summer insolation via nonlinear interaction with the global carbon cycle could also be a factor that forces the SAM in the Lunpola Basin (Ao et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…These processes further regulate the orbital‐scale changes of the capacity of the monsoon to transport moisture, such as tropical ocean water evaporation and lower‐tropospheric water vapor content affected by temperature, distance of moisture transport pathway from the ocean to the studied areas affected by sea‐level fluctuations and coastline, finally leading to orbital‐scale changes of intensity, northeastern edge, and precipitation extent of the SAM in the central TP (Ao et al., 2021; Nie et al., 2017). Alternatively, eccentricity modulates low‐latitude summer insolation via nonlinear interaction with the global carbon cycle could also be a factor that forces the SAM in the Lunpola Basin (Ao et al., 2021). Precession affects the seasonal cycle of incoming solar radiation and contributes to mid‐ to low‐latitude summer insolation on both hemispheric distributions, and is therefore considered a major control on changes in monsoon intensity (Mohtadi et al., 2016; Thomson et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be explained by the bundling of three precession cycles into a grand cycle, at the expense of the 23-ka spectral power (Liu et al, 2008). The 100-ka cycle also probably resulted from the bundling of two obliquity cycles, due to the weak and/or absent 100-ka cycle in the changes of East Asian monsoon and sea level from ∼1.7 Ma to MPT (Bintanja et al, 2005;Sun et al, 2010Sun et al, , 2019, despite the 100-ka cycle has been observed in some Oligocene and Miocene monsoon and benthic oxygen-carbon isotope records (Ao et al, 2021;Holbourn et al, 2018;Nie et al, 2017). Besides, a remarkable cycle of 200-ka has been observed (Figure 4c).…”
Section: Orbital Paces In Quaternary Redox History Of the Japan Seamentioning
confidence: 99%